Improving Employee Performance Through Work Discipline, Work Motivation and Work Environment at PT. Jayamandiri Gemasejati Bogor - Sudarijati Sudarijati; Samsuri Samsuri; Dinda Apriani Safina (Westscience Press, 2024)
The success of a company or organization is highly dependent on the activities and creativity of the resources within the company or organization. Human resources are one of the most important factors in a company to achieve company goals because the success or failure of the company in achieving its goals depends heavily on the ability of human resources or employee performance in completing their duties. Therefore, employee performance has an important role for the company to achieve its goals because good employee performance will produce good quality. This study aims to analyze and identify the effect of work discipline, work motivation, and work environment on employee performance at PT. Jayamandiri Gemasejati Bogor. The subjects of this study were 46 employees of PT. Jayamandiri Gemasejati Bogor as sample member. Determination of the sample using non-probability sampling with the sampling technique used is saturation sampling. The form of this research is descriptive and verification. The data analysis method used in this research is multiple linear regression analysis. The results of the study indicate that work discipline, work motivation, and work environment simultaneously and partially have a positive and significant effect on employee performance.